Chemical composition, in vitro antioxidant activity and α-glucosidase inhibitory effects of the essential oil and methanolic extract of Elsholtzia densa Benth. Issue 23 (1st December 2016) - Xuanji, Xue; Zengjun, Guo; Hui, Zhang; Xia, Liu; Jun, Luo; Dandan, Li; Jun, Li
Abstract: Elsholtzia densa Benth. is a traditional aromatic herb used in the pharmaceutical and flavouring industries. To analyse and compare the chemical composition, the oils and nonvolatile compounds in E. densa and Mosla chinensis Maxim. were extracted via hydrodistillation, solvent extraction or ultrasound-assisted extraction. Seventy-three volatile compounds in the volatile oil (0.35 ± 0.06%) obtained by E. densa via hydrodistillation were investigated by gas chromatography–mass spectrometer and compared based on different parameters. Also, the antioxidant activity and α-glucosidase inhibitory effects of the five sub-fractions of the methanolic extract were studied and the ethyl acetate sub-fraction (EC50  = 7.9 μg/mL) and petroleum ether sub-fraction (EC50  = 0.0955 mg/mL) showed the strongest activity, respectively. This study has provided a scientific basis for scientific collection, effective development, use of E. densa Benth., and suggested that it can be used as a potential source of antioxidants in food and a potential candidate for the management of type 2 diabetes mellitus. Abstract :